Early-onset androgenetic alopecia: a clue to the diagnosis of tricho-rhino-phalangeal syndrome. - Santos, T.S.; Frattini, S.C.M.; Fernandes de Almeida Pinto, K.; Llerena jr., J.C.; Melo, D.F. (European Journal of Pediatric Dermatology, 2016)
The tricho-rhino-phalangeal syndrome type 1 is a rare genetic multisystem disease characterized by the triad as follows: sparse and slow-growing hair, pear-shaped nose and bones disorders. The syndrome is characterized by autosomal dominant inheritance with high penetrance and variable expressivity. Here is reported a patient showing the clinical features of the syndrome in order to alert the dermatologists to cases of early-onset androgenetic alopecia for possible diagnosis of genetic diseases.